Abs. Issue 1 (November 2015) - Bychkov, V.; Nikitina, E.; Litviakov, N.
Abstract : Background: The aim of the study was to identify the factors that determine outcome and overall survival of HNC patients of Tomsk region. Materials and methods: Clinical data, morphological characteristics of tumors and outcomes were obtained for 91 patients. Data about lifestyle, food preferences, smoking history were obtained from the questionnaire ( n  = 35). All clinical samples were tested by AmpliSens HPV diagnostic kits (Russia) to determine prevalence of 12 high risk HPV types. Statistical analysis was performed using Kaplan–Meier method, Cox regression, Gehan test, Fisher test, Mann–Whitney and Kruskal–Wallis tests. Results: Gender, age, smoking status, alcohol consumption, distance from harmful factors, professional hazards and duration of its exposure as well as tumor criteria such as T, N, G, the presence of keratinization, invasion into the underlying tissues, HPV-infection, chemotherapy and/or radiation therapy and response to the treatment were assessed for HNC patients. It was shown that the two-year survival rate was about 70%, and the five-year survival rate was about 32%. There was strong correlation between decreased overall survival and increased alcohol consumption ( p  = 0.03) as well as regional lymph nodes status ( p  = 0.01). Patients with early tumor stages and N0 lymph node status as well as patients receiving chemotherapy and/or radiotherapy showed trend towards to better survival ( p  = 0.09, p  = 0.1, p  = 0.09, respectively). Overall survival of patients with lymph node metastasis was higher in case of early tumor stages ( p  = 0.08) and in patients who had no alcohol consumption history ( p  = 0.06). Cox regression analysis was used to obtain the model describing overall survival of patients. The model with the highest level of significance includes 3 factors-nodal metastases, the presence of keratinization and radiotherapy. It was shown that the risk of death was 4.2 and 2.6-fold higher in case of lymph node metastases and keratinized cancer, and 2.7-fold lower in case of radiotherapy. It was also shown that metastasis occurred more frequently in cases with invasion into the underlying tissue of a primary tumor ( p  = 0.04) and in cases with a low tissue grade ( p  = 0.02). Association of alcohol consumption with questionnaire data was studied. It was shown that men's preferably smokers consume alcohol more often than other patients ( p  = 0.006, p  = 0.02, respectively). Our data showed that HPV prevalence was higher in smokers ( p  = 0.04), and in patients with early tumor stages ( p  = 0.07). Furthermore, response to radiotherapy was better in HPV-positive patients compared to HPV-negative cases ( p  = 0.09). Better response to radiotherapy showed the group of patients who received dose higher than 45 Gy ( p  = 0.03) and who had no lymph node metastases( p  = 0.05). Conclusion: Our data showed that metastasis to lymph nodes and alcohol consumption are the main factors that affect mortality in HNC patients of Tomsk region.